6-Hexyl-1, 2, 4, 5-tetrazinane-3-thione: Flotation selectivity and mechanism to copper sulfide mineral. (15th June 2020) - Liu, Jun; Liu, Guangyi; Yang, Xianglin; Dong, Yan; Zhang, Zhiyong
Graphical abstract: The superior flotation affinity and selectivity of 6-hexyl-1, 2, 4, 5-tetrazinane-3-thione towards chalcopyrite in comparison to sodium hexyl xanthate. Highlights: 6-Hexyl-1, 2, 4, 5-tetrazinane-3-thione was first used as chalcopyrite collector. HTT exhibited stronger hydrophobization to chalcopyrite than hexyl xanthate. HTT owned the strong electron-acceptance and moderate electron-donation power. HTT's flotation affinity and selectivity to CuFeS2 was better than those of xanthate. HTT agglomerates covered chalcopyrite surface due to form Cu-N and Cu-S bonds. Abstract: The floatability of chalcopyrite and pyrite by using 6-hexyl-1, 2, 4, 5-tetrazinane-3-thione (HTT) as a collector was evaluated in the paper. In comparison with the traditional-type collector sodium hexyl xanthate (SHX), HTT exhibited the favorable flotation affinity toward chalcopyrite and superior selectivity for flotation separation of chalcopyrite from pyrite. UV spectra demonstrated that HTT preferred to react with cupric/cuprous ions rather than ferric/ferrous ions. Contact angle results indicated a stronger hydrophobization of HTT towards chalcopyrite than SHX. DFT (density functional theory) calculations recommended that HTT had a stronger electron-acceptance power to the d-orbital electrons of interface copper atoms on chalcopyrite and a slightly weaker electron-donation ability than HX − anion, which improved the flotation selectivity of HTT toward chalcopyrite against pyrite. AFM images displayed a dense cover of HTT agglomerates on the whole surface of chalcopyrite. Zeta potential and XPS confirmed the bonding interaction of the interface copper atoms of chalcopyrite with the N and S atoms of HTT's tetrazinane-thione group.